Management of Repository Management in the Technical Implementation Unit of the Library of Datokarama State Islamic University Palu - Mohammad Irfan; Iskandar; Idris (Jurnal Sinar Manajemen, 2025)
This study aims to determine the management of Repository management at the UPT Library UIN Datokarama Palu. Using a descriptive qualitative approach, this research involved direct observation, in-depth interviews with the vice rector for academic affairs and institutional development, the head of the UIN Datokarama Palu Library, and the library repository manager, as well as documentation analysis. The results of this study explain that the library uses a repository as a repository for scientific works produced by the academic community to facilitate information searches. There are several repository development plans, one of which is the thesis collection, namely by changing the appearance of the thesis which is similar to the book form so that it has an attractive appearance. To realize this, the library coordinates in accordance with the organizational structure of the UIN Datokarama Palu library, and is carried out based on existing SOPs and uses policy references that have been approved by the rector. Then repository management activities carried out in the library such as inputting, processing and maintenance. And this activity is supervised by the quality assurance body, internal supervisory unit and direct supervision from the head of the library to the librarian. Supporting factors in carrying out repository management activities at UIN Datokarama Palu Library come from the academic community such as students, lecturers, who deposit their scientific papers, then the facilities and infrastructure provided for managers are quite fulfilled but still require some additional adequate technology. while the inhibiting factors faced by managers such as, when maintaining the repository website, inadequate human resources, network problems and collections that have not been deposited by the academic community.